Reply to "Comment on 'U‐Pb and Hf Isotope Analysis of Detrital Zircons From Mesozoic Strata of the Gravina Belt, Southeast Alaska' by Yokelson Et Al. (2015)". Issue 11 (3rd November 2017) - Gehrels, George E.; McClelland, William C.; Yokelson, Intan
Key Points: The western Gravina belt is depositionally tied to the outboard Alexander terrane The eastern Gravina belt is depositionally tied to the inboard Yukon‐Tanana and Taku terranes There is no evidence of a subduction zone of Late Jurassic‐Early Cretaceous age between the eastern and western Gravina belts